2022
DOI: 10.1155/2022/6777409
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Pulsatilla chinensis Total Saponin Extracts via Quantitative Analysis of Multicomponents by Single Marker Method Combined with Systematic Quantified Fingerprint Method

Abstract: Chinese medicine extracts are complex in composition. The combination of the quantitative analysis of multicomponents by single marker (QAMS) and the systematic quantified fingerprint method (SQFM) can be used for better quantitative analysis. The contents of Pulsatilla saponin D, Pulsatilla saponin A, Pulsatilla saponin F, and oleanolic acid 3-o-β-d-pyranoglucosyl-(1⟶4)-β-d-pyranoglucosyl-(1⟶3)-α-l-pyridine rhamnosyl-(1⟶2)-α-l-pyranosine arabinoside (B9) were determined by HPLC and QAMS. The methodological ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…α-hederin, a pentacyclic triterpenoid saponin derived from Pulsatilla chinensis (Bunge) Regel (Ranunculaceae), has demonstrated effectiveness in various applications such as antitumor, anti-fungal, and insecticidal properties (Adamska et al, 2019;Chen et al, 2022). In this study, we found that α-hederin triggered oxidative stress events, including ROS accumulation and GSH depletion.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…α-hederin, a pentacyclic triterpenoid saponin derived from Pulsatilla chinensis (Bunge) Regel (Ranunculaceae), has demonstrated effectiveness in various applications such as antitumor, anti-fungal, and insecticidal properties (Adamska et al, 2019;Chen et al, 2022). In this study, we found that α-hederin triggered oxidative stress events, including ROS accumulation and GSH depletion.…”
Section: Discussionmentioning
confidence: 63%
“…In the meantime, studies have tried to find effective phytochemicals or derivatives targeting the Nrf2/KEAP1 axis, which plays a crucial role in tumor development (Deshmukh et al, 2017; Fourquet et al, 2010; Yamamoto et al, 2008). α‐hederin, a pentacyclic triterpenoid saponin derived from Pulsatilla chinensis (Bunge) Regel (Ranunculaceae), has demonstrated effectiveness in various applications such as antitumor, anti‐fungal, and insecticidal properties (Adamska et al, 2019; Chen et al, 2022). In this study, we found that α‐hederin triggered oxidative stress events, including ROS accumulation and GSH depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of QAMS and chromatographic fingerprints technique enable simultaneous determinations of multiple target constituents and common peaks, which could largely improve the efficiency and comprehensiveness of the quality control of TCMs. Nowadays, the QAMS-fingerprint method has been successfully established and applied in many TCMs, such as Psoraleae Fructus (Luan et al, 2018), Radix Astragali (Huang et al, 2018), Rhubarb (Dou et al, 2021), Berberidis Cortex (Su et al, 2022), and Pulsatilla Chinensis (Chen et al, 2022), but there has been no relevant report in Bupleuri Radix. In addition, the current fingerprint method for Bupleuri Radix has a detection time of up to about 1.5 h, which is unable to applicate (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…5 Saponins can be divided into steroid saponins and triterpene saponins according to their glycosides. 6 Steroidal saponins are found in monocotyledons such as panaxo saponins 7 and Silan saponins, 8 while triterpene saponins are found in dicotyledons such as bailey saponins 9 and soy saponins. 10 Soy saponins, in particular, have good amphiphilic properties with their polar water-soluble sugars linking to nonpolar nonsugar substances.…”
Section: Introductionmentioning
confidence: 99%